Epigenetics Modifications and Therapeutic Prospects in Human Thyroid Cancer - Catalano, Maria Graziella; Fortunati, Nicoletta; Boccuzzi, Giuseppe (Frontiers in Endocrinology, 2012)
At present no successful treatment is available for advanced thyroid cancer, which comprises poorly differentiated, anaplastic, and metastatic or recurrent differentiated thyroid cancer not responding to radioiodine. In the last few years, biologically targeted therapies for advanced thyroid carcinomas have been proposed on the basis of the recognition of key oncogenic mutations. Although the results of several phase II trials look promising, none of the patients treated had a complete response, and only a minority of them had a partial response, suggesting that the treatment is, at best, effective in stabilizing patients with progressive disease. “Epigenetic” refers to the study of heritable changes in gene expression that occur without any alteration in the primary DNA sequence. The epigenetic processes establish and maintain the global and local chroma¬tin states that determine gene expression. Epigenetic abnormalities are present in almost all cancers and, together with genetic changes, drive tumour progression. Various genes involved in the control of cell proliferation and invasion (p16INK4A, RASSF1A,PTEN, Rap1GAP, TIMP3, DAPK, RARβ2, E-cadherin, and CITED1) as well as genes specific of thyroid differentiation (Na+/I- symport, TSH receptor, pendrin, SL5A8, and TTF-1) present aberrant methylation in thyroid cancer. This review deals with the most frequent epigenetic alterations in thyroid cancer and focuses on epigenetic therapy, whose goal is to target the chromatin in rapidly dividing tumour cells and potentially restore normal cell functions. Experimental data and clinical trials, especially using deacetylase inhibitors and demethylating agents, are discussed.